Multiferroics Made via Chemical Co-Precipitation That Is Synthesized and Characterized as Bi(1−x)CdxFeO3 - Syed Zain Mehmood; Mubashar Arshad; Fahad M. Alharbi; Sayed M. Eldin; Ahmed M. Galal (Inorganics, 2023)
Cd-doped BiFeO3 powders, with varying doping concentrations of Cd (Bi(1−x)CdxFeO3, where x = 0–0.3), were prepared through a facile chemical co-precipitation method and calcinated at 550 °C in the air. The BiFeO3 has a rhombohedral crystal structure, which changes to an orthorhombic crystal structure with an increase in Cd doping. The presence of dopant has also altered the bandgap of material suppressing it from 2.95 eV to 2.51 eV, improving the visible light absorption. Vibrating sample magnetometry (VSM) confirmed stronger ferromagnetic character for Bi0.7Cd0.3FeO3 with a coercivity of 250 Oe, and remnant magnetization was 0.15 emu/g, which is because of the misalignment of the two sublattices of perovskite structure after doping resulting in the imbalanced magnetic moment giving rise to net nonzero magnetic behavior. The particle size reduction is observed with an increase in the doping concentration of Cd.